De-securitizing through Diplomacy: De-sectarianization and the View from the Islamic Republic - Nasirzadeh, Samira (The review of faith & international affairs, 2020)
As a country often defined in terms of its sectarian identity, the Islamic Republic provides an interesting test case for the notion of de-sectarianization. Iran's position as the pre-eminent Shi'a-majority power in the region has presented it with opportunities to draw on its historical confessional linkages, but it also singles it out as a unique case. Building upon the theoretical and conceptual frameworks provided by the sectarianization thesis, de-securitization, and insights from diplomatic studies, this paper presents empirical examples from Iran's Eurasian and religious diplomacy that provide a potential starting point for de-sectarianization of the region's fractious international politics.